2015
DOI: 10.1038/ncomms9654
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt-centred boron molecular drums with the highest coordination number in the CoB16− cluster

Abstract: The electron deficiency and strong bonding capacity of boron have led to a vast variety of molecular structures in chemistry and materials science. Here we report the observation of highly symmetric cobalt-centered boron drum-like structures of CoB16−, characterized by photoelectron spectroscopy and ab initio calculations. The photoelectron spectra display a relatively simple spectral pattern, suggesting a high symmetry structure. Two nearly degenerate isomers with D8d (I) and C4v (II) symmetries are found com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
189
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 215 publications
(200 citation statements)
references
References 49 publications
9
189
0
2
Order By: Relevance
“…This has been seen very recently in the experimental work of Pollak et al, [2] who found 16 Cs···F contacts in Cs[H2NB2(C6F5)6], and that by Popov et al in CoB16 -, [3] and has also been predicted theoretically by Gu et al [4] for M@Li16 (M = Ca, Sr, Ba, Ti, Zr and Hf). The record for the actinide elements stood at 14 for many years (in U(BH4)4), [5] but is now 15, established experimentally by Daly et al for Th(H3BNMe2BH3)4, [6] although the same authors used density functional theory (DFT) to predict that in the gas phase the number of Th···H contacts could rise to 16. All of these contributions make reference to the work of Hermann et al [7] who, in 2007, published in this journal a DFT survey of the geometric structures of Pb 2+ coordinated by He atoms.…”
supporting
confidence: 55%
“…This has been seen very recently in the experimental work of Pollak et al, [2] who found 16 Cs···F contacts in Cs[H2NB2(C6F5)6], and that by Popov et al in CoB16 -, [3] and has also been predicted theoretically by Gu et al [4] for M@Li16 (M = Ca, Sr, Ba, Ti, Zr and Hf). The record for the actinide elements stood at 14 for many years (in U(BH4)4), [5] but is now 15, established experimentally by Daly et al for Th(H3BNMe2BH3)4, [6] although the same authors used density functional theory (DFT) to predict that in the gas phase the number of Th···H contacts could rise to 16. All of these contributions make reference to the work of Hermann et al [7] who, in 2007, published in this journal a DFT survey of the geometric structures of Pb 2+ coordinated by He atoms.…”
supporting
confidence: 55%
“…The discovery of the first double-ring (DR) tubular B 20 and the experimental confirmation of the double-ring (DR) tubular B n + monocations (n = 16–25)24, on the other hand, unveils another important domain in the structural evolution of boron clusters. The recent experimental observation of the metal-centered DR tubular D 8 d Co©B 16 − with the coordination of 16 further indicate that doping boron clusters with a transition metal makes an earlier structural transition from 2D planar to 3D tubular in boron clusters25. Triple-ring (TR) tubular B 3n (n = 8–32) have also been predicted to be competitive isomers at DFT26.…”
mentioning
confidence: 97%
“…7b For the CoB 16 − species, which has been generated in the gas phase by laser vaporization of a Co−B target, a drum-like structure of 16 4-fold B−B bonded boron atoms around a central Co atom has been calculated. 8 To achieve extremely high CNs > 12 in Werner-type complexes of non-hydrogen donors requires a large metal center of low electrophilicity and small donor atoms of low donor strength. Cs + is the largest singly charged monatomic cation and therefore of lowest electrophilicity.…”
mentioning
confidence: 99%
“…(c) The square gyrobicupola (Johnson solid J29, D 4d symmetry) has been established for the Ag 16 (PSi t Bu 3 )8 32a and [Cu 16 S 10 ] 4−32b clusters but features only 18 faces. (d) The disphenocingulum (J90; 4 squares, 20 triangles, 38 edges; D 2d symmetry) agrees with 1 in that it represents a 24-hedron, but the spatial arrangement of the faces does not meet the situation given in 1.…”
mentioning
confidence: 99%